New record of Brachycyrtus Kriechbaumer, 1880 (Hymenoptera: Ichneumonidae) from Venezuela and notes about their association with some chrysopid species - Yanez, Astrid; Sosa-Duque, Francisco J.; Díaz, Francisco (Entomological Communications, 2020)
Brachycyrtus pretiosus Cushman, 1936 is recorded from Venezuela for the first time. The green-lacewings species Ceraeochrysa valida (Banks, 1851) and Ceraeochrysa fairchildi (Banks, 1946) are considered as the first known recorded hosts of Brachycyrtus cosmetus (Walkley, 1956). Illustrations of the studied Brachycyrtus spp. Adults, final larval instar cephalic structures of B. cosmetus and maps with geographical distribution are provided.